Child maltreatment: a national survey of reports and fatalities - McCurdy, Karen (Journal of interpersonal violence, 1994)
This article examines the scope of the child maltreatment problem in the United States. Representatives of child protective service agencies in each state and the District of Columbia were interviewed to obtain current estimates of child maltreatment reports and fatalities. The results of the survey indicate that rates of reported and substantiated cases of child maltreatment as well as confirmed child deaths due to abuse or neglect have steadily increased over the past 8 years. Evidence shows that very young children face the greatest risk of dying from maltreatment. Other findings such as specific characteristics of the reported population, differences in states' reporting procedures, and changes in funding of child welfare services are presented along with a discussion of policy implications